Quantitative therapy response assessment by volumetric iodine-uptake measurement: initial experience in patients with advanced hepatocellular carcinoma treated with sorafenib - Dai, Xu; Schlemmer, Heinz-Peter; Schmidt, Bernhard; Höh, Karolin Julia; Xu, Ke; Ganten, Tom M.; Ganten, Maria-Katharina (European journal of radiology, 2013)
Objectives - To investigate the volumetric iodine-uptake (VIU) changes by dual-energy CT (DECT) in assessing the response to sorafenib treated hepatocellular carcinoma (HCC) patients, compared with AASLD (American Association for the Study of Liver Diseases) and Choi criteria. - Materials and methods - Fifteen patients with HCC receiving sorafenib, monitored with contrast-enhanced DECT scans at baseline and a minimum of one follow-up (8-12 weeks) were retrospectively evaluated. 30 target lesions in total were analyzed for tumor response according to VIU and adapted Choi criteria and compared with the standard AASLD. - Results - According to AASLD criteria, 67% target lesions showed disease control: partial response (PR) in 3% and stable disease (SD) in 63%. 33% lesions progressed (PD). Disease control rate presented by VIU (60%) was similar to AASLD (67%) and Choi (63%) (P>0.05). For disease control group, change in mean VIU was from 149.5±338.3mg to 108.5±284.1mg (decreased 19.1±42.9%); and for progressive disease group, change in mean VIU was from 163.7±346.7mg to 263.9±537.2mg (increased 230.5±253.1%). Compared to AASLD (PR, 3%), VIU and Choi presented more PR (33% and 30%, respectively) in disease control group (P<0.05). VIU has moderate consistency with both AASLD (kappa=0.714; P<0.005) and Choi (kappa=0.648; P<0.005), while VIU showed a better consistency and correlation with AASLD (kappa=0.714; P<0.005; r=0.666, P<0.005) than Choi with AASLD (kappa=0.634, P<0.005; r=0.102, P=0.296). - Conclusion - VIU measurements by DECT can evaluate the disease control consistent with the current standard AASLD. Measurements are semi-automatic and therefore easy and robust to apply. As VIU reflects vital tumor burden in HCC, it is likely to be an optimal tumor response biomarker in HCC.
Available online: 11 December 2012
Gesehen am 02.06.2021